2014
DOI: 10.1634/theoncologist.2013-0209
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Lifetime Costs Associated With First-Line Bevacizumab Use in Older Patients With Metastatic Colorectal Cancer

Abstract: Introduction. The objective of this study was to investigate clinical effectiveness and incremental lifetime costs associated with first-line bevacizumab in older patients with metastatic colorectal cancer (mCRC). Methods. Patients diagnosed with mCRC in 2004-2007 were identified from the Surveillance, Epidemiology, and End ResultsMedicare database and stratified by first-line treatment (no chemotherapy [CTx], CTx alone, CTx plus bevacizumab). The impact of first-line bevacizumab on survival was investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Although our results indicate that targeted therapies may have reduced early mortality, treatment with targeted therapy was not associated with a lower risk of death at 36 months. These findings are consistent with existing data, the improvement in OS by targeted therapies not being significant in many studies, even in younger populations . Nevertheless, a relevant evaluation of the effectiveness of cancer treatment in older adults should be based on other end points such as progression‐free survival, quality of life, and maintenance of independence .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although our results indicate that targeted therapies may have reduced early mortality, treatment with targeted therapy was not associated with a lower risk of death at 36 months. These findings are consistent with existing data, the improvement in OS by targeted therapies not being significant in many studies, even in younger populations . Nevertheless, a relevant evaluation of the effectiveness of cancer treatment in older adults should be based on other end points such as progression‐free survival, quality of life, and maintenance of independence .…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with existing data, the improvement in OS by targeted therapies not being significant in many studies, even in younger populations. 23,[25][26][27][28][29] Nevertheless, a relevant evaluation of the effectiveness of cancer treatment in older adults should be based on other end points such as progression-free survival, quality of life, and maintenance of independence. 20 Data regarding these end points are currently lacking regarding the comparison of treatment with or without targeted therapy in real-life settings.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective database analysis found that adding bevacizumab to chemotherapy in the first-line setting cost $75,303/LY. 17 The lower ICER in the retrospective study, compared to the Markov model, may be due to the greater bevacizumab efficacy seen in the retrospective study. 3 …”
Section: Resultsmentioning
confidence: 94%
“…Observational studies of bevacizumab with irinotecan have also reported mixed results; Ruiz-Millo and colleagues reported increased costs of €12,700 per patient (CAD$17,300), with no significant improvement in progression-free survival in a small hospital setting, 35 while Shankaran and colleagues reported an ICER of US$75,303 (CAD$98,700) using linked SEER-Medicare data. 36…”
Section: Discussionmentioning
confidence: 99%